2020
DOI: 10.21203/rs.3.rs-121509/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic analysis of breast cancer patients sensitive and resistant to chemotherapy: Looking for overall survival and drug resistance biomarkers 

Abstract: Neoadjuvant chemotherapy is one important therapeutic strategy for breast cancer with the drawback of resistance development. Chemotherapy has adverse effects that combined with resistance could contribute to lower overall survival. This work aimed to evaluate the molecular profile of patients who received neoadjuvant chemotherapy to discover differentially expressed genes (DEGs) that could be used as biomarkers of chemotherapy response and overall survival. Breast cancer patients who received neoadjuvant chem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
1
4
1
Order By: Relevance
“…[12] Besides, another study reveals that KRT15 overexpression is associated with tumor metastasis in breast cancer patients. [17] In the present study, KRT15 protein expression was correlated with the occurrence of lymphovascular invasion and more advanced FIGO stage; meanwhile, KRT15 mRNA expression was correlated with the more advanced FIGO stage and marginally associated with the occurrence of stromal cervical invasion. Possible explanations could be that: KRT15 upregulation is associated with enhanced cancer stem cell property which exhibits a strong infiltration capacity; thus, KRT15 overexpression is linked with the occurrence of lymphovascular invasion and stromal cervical invasion in EC patients.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…[12] Besides, another study reveals that KRT15 overexpression is associated with tumor metastasis in breast cancer patients. [17] In the present study, KRT15 protein expression was correlated with the occurrence of lymphovascular invasion and more advanced FIGO stage; meanwhile, KRT15 mRNA expression was correlated with the more advanced FIGO stage and marginally associated with the occurrence of stromal cervical invasion. Possible explanations could be that: KRT15 upregulation is associated with enhanced cancer stem cell property which exhibits a strong infiltration capacity; thus, KRT15 overexpression is linked with the occurrence of lymphovascular invasion and stromal cervical invasion in EC patients.…”
Section: Discussionsupporting
confidence: 50%
“…[23,24] Apart from the above-mentioned relevance of KRT15 with clinical features, its upregulation also links with an unsatisfying survival profile in breast cancer and non-small cell lung cancer. [17,25] Herein, the KRT15 overexpression was marginally correlated with accumulating DFS and OS in EC patients, which was estimated by Kaplan-Meier method and analyzed by log-rank test, whereas further adjusted multivariate Cox's regressions showed that tumor KRT15 protein (high vs low) was independently correlated with poor DFS and OS. Possible explanations could be that KRT15 overexpression is linked with enhanced cancer stem cell properties and therefore lined with a higher recurrence rate; thus, KRT15 overexpression is correlated with poor survival indexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, low expression of this gene was associated with a worse prognosis for OS. This gene has already been reported to predict treatment response and OS (Sinn et al, 2021;Barron-Gallardo et al, 2022). ATF6B has two ensemble IDs (ENSG00000228628 and ENSG00000213676).…”
Section: Discussionmentioning
confidence: 93%
“…A previous study was conducted to determine biomarkers of response to neoadjuvant chemotherapy in patients with breast cancer (GSE162187) (Barron-Gallardo et al, 2022). In this study, HER2+ samples were taken and included in the RNA-seq analysis; five samples were from patients categorized as resistant to treatment, and three samples were from patients sensitive to treatment.…”
Section: Resultsmentioning
confidence: 99%